THE THE PECULIARITIES OF THE ELECTORAL ARENA OF POLITICAL PARTICIPATION IN CONTEMPORARY RUSSIAN SOCIETY - A. A. Lavrikova (Современная наука и инновации)
The complications occurring in political systems contribute to the differentiation of political practices and their isolation into separate areas, within which the main interactions (cooperation I competition) of the subjects of political participation are realized. Each of the emerging arenas of political participation is a relatively independent and holistic ensemble of relations, which operates according to the relevant rules and regulations, but is able in certain situations to intersect with other arenas. It is characterized by relative isolation and autonomy, the presence of specific political practices of participation.